An area-based description of closed books in general practices in Aotearoa New Zealand - Jacqueline Cumming; Mona Jeffreys; Nisa Mohan; Maite Irurzun-Lopez; Megan Pledger (CSIRO Publishing, 2023)
Introduction In Aotearoa New Zealand, patients can enrol in a general practice for their primary health care. When a general practice no longer enrols new patients this is known as 'closed books'. We examined which District Health Board (DHB) districts were most affected and what characteristics of general practices and DHB districts were associated with closed books. Methods Maps were used to display the distribution of closed books general practices. Linear regression and logistic regression were used to look at the association between DHB or general practice characteristics and closed books. Results There were 347 (33%) general practices that had closed books in June 2022. Canterbury DHB (n = 45) and Southern DHB (n = 32) had the greatest number of closed books general practices, while Wairarapa DHB (86%), Midcentral DHB (81%) and Taranaki DHB (81%) had the greatest percentage. Consultation fees (P  Conclusion The problem of closed books is felt across the country but has a larger impact in the middle-lower North Island. This influences access to primary health care enrolment for patients in terms of travel distance, time, and cost. Consultation fees were strongly associated with closed books. This suggests there may be an income threshold above which general practices can afford to close their books if they reach capacity.